BASIC IDEAS FOR DETERMINING DEATH CRIMINAL THREATS IN LAW NUMBER 35 OF 2009 ON NARCOTICS - Malik, Faissal (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2019)
The basic idea of ​​using the threat of capital punishment against perpetrators of